2016
DOI: 10.3928/01484834-20160114-04
|View full text |Cite
|
Sign up to set email alerts
|

Power of Peer-Assisted Learning: An Interdisciplinary Mobility Laboratory Experience

Abstract: Both groups reported that the PAL strategy was successful in achieving the intended goals of improved interprofessional understanding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Furthermore, they perceived the lessons better suited to the level of the tutees 7 . Additionally, peer‐tutoring or peer‐teaching programs have shown that students felt that peers were often as helpful as faculty and knowledge was improved after sessions taught by peers 2,8 . Similar results were found in courses other than didactic courses, such as clinical or lab courses that involve hand skills 8 …”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…Furthermore, they perceived the lessons better suited to the level of the tutees 7 . Additionally, peer‐tutoring or peer‐teaching programs have shown that students felt that peers were often as helpful as faculty and knowledge was improved after sessions taught by peers 2,8 . Similar results were found in courses other than didactic courses, such as clinical or lab courses that involve hand skills 8 …”
Section: Introductionmentioning
confidence: 58%
“…The purpose of this study was to provide an overview and initial program assessment of a student peer‐tutoring program at the University of Pittsburgh School of Dental Medicine. Data from the current study is in alignment with documented benefits of peer‐tutoring programs for tutees 3‐8 ; however, this report presents baseline data on the benefits of the program for the tutor, strengths of the program, and participants’ suggestions for improvement.…”
Section: Discussionmentioning
confidence: 99%